How images about emerging economies influence the willingness to accept expatriate assignments - Eccher, U.; Duarte, H. (International Journal of Human Resource Management, 2018)
Countries’ image is a multifaceted construct. Its symbolic dimensions have shown to play an important role both on consumer behavior and on the attraction that organizations can have during the recruitment process. This paper offers a comprehensive model of international mobility decisions encompassing the antecedents and consequences of perceptions about emerging economies, proposing that country image depends on individuals’ background and social identities. In this context, countries’ evaluations can play a major role on influencing the willingness to accept expatriate job offers. We used a within-subject design asking for opinions about hypothetical job offers on six particular host countries: Algeria, Democratic Republic of Congo, Argentina, Chile, Angola and Mozambique. Survey results from more than 500 engineers, (125 French nationals, 121 Spanish and 131 Portuguese, with the remaining 138 coming from 42 different countries, yet working in 1 of the 3 above-mentioned European countries), evidence, that language proficiency influences the evaluation of specific expatriate locations. Our results also convey the critical role of the perceived level of safety and cultural attraction in predicting the willingness to accept expatriate job offers. We conclude by discussing the theoretical and practical implications for human resource management.